ANALISIS PENGENDALIAN PERSEDIAAN MINYAK GORENG PADA UNIT PENJUALAN DI PT. SUBUR LUMINTU DI SAMARINDA - Herwanthy, Linda Maria (EKONOMIA, 2019)
LINDA MARIA HERWANTHY : Analysis of Control ofÂ cooking oil supplies in the sales unit in PT. Subur Lumintu at Samarinda, under the guidance of MR. Eddy Soegiarto as counselor I and Mrs. Andi Indrawati as counselor II.Large inventory of goods results in large ordering costs and stroge costs of goods inventory which of course reduces the profitsthat should be achieved by the company. We recommend that the inventory of goods that is too small causes the frequency of purchasing goods to be higher,as a result the costs associated with the purchase of these goods are high.PT. SuburÂ Lumintu in Samarinda by applying the EOQ method to determine the determination of raw material inventory, safetyÂ stockÂ and can determine when reorder point performed and the amount of raw material ordering which minimizes total inventory costs.Â The ordersmade by the company are uncertain because they see supplies still in the warehouse. This study aims to determine how much the economic order amount of cooking oil supplies for each order that can be done by PT. Subur Lumintu in Samarinda.The results of the analysis of the economic amount that should be carried out by PT. Subur Lumintu for the raw material of cooking oil must follow the calculation of EOQ in each order and re-order if the value of the inventory has reached the predetermined ROP calculation. With the EOQ method, PT. Subur Lumintu can find out the costs of the companyâ€™s inventory has been spared or not to maintain the availabiliy of fortune cooking oil for the sake of the continuity of the production process.Â Subur Lumintu company is expected to use the EOQ method, the thing that must be considered is the stability of demand and the supply of raw materials for cooking oil â€œFortuneâ€, so that Subur Lumintu company can save inventory costs, so that the fertile soil will achieve optimum profit.